TINJAUAN EKONOMI SYARIAH TERHADAP SISTEM PENGAWASAN PENGELOLAAN RENSTRA APBDDESA - Risno Risno (Institut Agama Islam Negeri (IAIN) Bone, 2022)
The purpose of this research to identify and explain the monitoring system for the management of the Awang Cenrana Strategic Plan APBDesa in terms of an Islamic economic perspective with a field study approach with a qualitative-descriptive design. Data is collected through the library (library research) and goes directly to the field (field research).The results of this study indicate that the oversight system for the management of the Awang Cenrana Strategic Plan APBDesa has basically been carried out well. If viewed from a sharia perspective on the oversight system for the management of the Awang Cenrana Restra APBDesa, it is found that in the perspective of trustworthiness, honesty and truth, village leaders such as the Village Head, Secretary and Head of Keungan Awang Cenrana Village have fulfilled these three criteria. The implication of this research is that in the sharia economic perspective of budget management as in APBDesa, the nature of trust, honesty, truth and justice is absolute, which cannot be carried out except by applying the principle of budget transparency. Therefore conducting budget transparency is mandatory.